Red fluorescent material, preparation method and application thereof
By adopting a core-shell structure in the red fluorescent material, the core is a silicon-aluminum-based nitride with high Sr content and the outer shell is a silicon-aluminum-based nitride with high Ca content, the problem of existing red fluorescent powder being susceptible to water oxygen erosion is solved, and the comprehensive performance with high luminescence efficiency and high reliability is achieved.
Patent Information
- Application Number
- CN202311147084.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-09-06
AI Technical Summary
The existing silicon-aluminum-based nitride red phosphor is susceptible to water oxygen erosion during service, resulting in structural collapse and activator ions deactivation, affecting the optical performance of white LEDs.
The red fluorescent material adopts a core-shell structure, the core chemical composition is A1mM1a-mAlbSicNd:xEu, and the shell chemical composition is A2nM2a-nAlbSicNd:yEu. By adjusting the ratio of Sr and Ca, a core with high Sr content and a shell with high Ca content is formed, which jointly improves the luminescence efficiency and reliability of the material.
The red fluorescent materials have achieved high luminous efficiency and high reliability, and improved the light efficiency and weather resistance of white LEDs, especially under high temperature and high humidity conditions, which have higher light efficiency and better light efficiency maintenance effects.
Smart Images

Figure CN117186884B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of luminescent materials, and in particular to a red fluorescent material, a preparation method and application thereof. Background Art
[0002] As a new generation of lighting devices, white light LED (White Light Emitting Diode) has been widely used in general lighting, traffic light indication, display, medical treatment, modern agriculture and other fields due to its advantages of high light efficiency, low energy consumption, long life and no pollution. The mainstream implementation method of white light LED is a single ultraviolet / near ultraviolet / blue light chip compounded with blue / yellow-green / red phosphor. This solution has the advantages of high technical maturity, simple and easy solution and relatively low cost. As a key material for white light LED, phosphor directly determines the light source quality of the packaged device, among which red phosphor is the guarantee of the device's color rendering ability. Compared with sulfide red phosphor and oxide red phosphor, silicon aluminum-based nitride phosphor has higher luminous efficiency, wider emission spectrum and better safety performance, and is now the mainstream commercial red phosphor.
[0003] With the expansion of white light LED application areas and the innovation of general lighting needs, white light LEDs are developing towards higher light efficiency and better color rendering quality. At the same time, the power density inside lighting devices is also constantly increasing, which puts higher requirements on the reliability of phosphor powder. The reliability of silicon aluminum-based nitride red phosphor is particularly critical. It determines the maintenance of the light efficiency of white light LEDs and the anti-color drift performance of the device under high temperature and high humidity service conditions. However, the existing silicon aluminum-based nitride red phosphor is susceptible to corrosion by water and oxygen during service, resulting in structural collapse and activator ion inactivation, which in turn affects the optical performance of the device. Therefore, it is urgent to develop highly reliable silicon aluminum-based nitride red phosphors. Summary of the invention
[0004] The main purpose of the present invention is to provide a red fluorescent material, a preparation method and application thereof, so as to solve the problem that the red fluorescent material in the prior art cannot have both high luminous efficiency and high reliability.
[0005] In order to achieve the above object, according to one aspect of the present invention, a red fluorescent material is provided. The red fluorescent material is a core-shell structure, including a core and a shell coated on the surface of the core. The chemical composition of the core is expressed as A1 m M1 a- m Al b Si c N d :xEu, the chemical composition of the shell is expressed as A2 n M2 a-n Al b Si cN d :yEu, wherein 0.92≤a≤1.2, 0.8≤b≤1.2, 0.8≤c≤1.2, 2.8≤d≤3.2; wherein A1 and A2 are independently selected from one or more of Ba, Mg, Li, Na and K, respectively, in the inner core, 0≤m≤0.02, 0.0001≤x≤0.08; M1 includes Sr and Ca, with the molar number of M1 being 1, the molar ratio of Sr to M1 is denoted as h, 0.6≤h<1; in the outer shell, 0≤n≤0.02, 0≤y≤0.03; M2 includes Sr and Ca, with the molar number of M2 being 1, the molar ratio of Ca to M2 is denoted as k, 0.6≤k≤1.
[0006] Furthermore, A1 and / or A2 is Na; and / or in the inner core, 0.8≤h≤0.99; and / or in the outer shell, 0.8≤k≤1.
[0007] Furthermore, the diameter of the inner core is 4 to 32 μm; and / or the thickness of the outer shell is 0.3 to 7 μm.
[0008] Furthermore, the diameter of the inner core is 10-25 μm, and the ratio of the thickness of the outer shell to the diameter of the inner core is (0.03-0.2):1.
[0009] Furthermore, in the shell, y is 0, and the ratio of the thickness of the shell to the diameter of the core is (0.01-0.1):1.
[0010] According to another aspect of the present invention, a method for preparing the above-mentioned red fluorescent material of the present invention is provided, comprising the following steps: step S1, weighing and mixing one or more nitrides, oxides and fluorides of Sr, one or more nitrides, oxides and fluorides of Ca, one or more nitrides, oxides and fluorides of Al, one or more nitrides, oxides and fluorides of Si, one or more nitrides, oxides and fluorides of Eu, and one or more nitrides, oxides, fluorides and carbonates of optional alkali metals, and one or more nitrides, oxides, fluorides and carbonates of optional alkaline earth metals according to the molar ratio of each element in the chemical composition of the inner core to obtain a first mixture; weighing and mixing according to the molar ratio of each element in the chemical composition of the outer shell to obtain a second mixture; step S2, performing a first calcination on the first mixture to obtain a first calcination product; step S3, mixing the first calcination product with the second mixture and performing a second calcination to obtain a red fluorescent material; wherein the alkali metal includes one or more of Li, Na and K, and the alkaline earth metal includes Ba and / or Mg.
[0011] Further, in step S2, the temperature of the first calcination is 1500-2000°C, the time is 5-12 hours, and the atmosphere is a nitrogen and / or hydrogen atmosphere; preferably, the temperature of the first calcination is 1750-1930°C; and / or in step S3, the temperature of the second calcination is 1300-1900°C, the time is 4-10 hours, and the atmosphere is a nitrogen and / or hydrogen atmosphere; preferably, the temperature of the second calcination is 1500-1700°C.
[0012] Furthermore, the nitride of Al is AlN, the nitride of Si is Si3N4, and the nitride of Eu is EuN; preferably, the preparation method also includes: post-processing the first calcined product, the post-processing including one or more of ball milling, acid and / or alkaline solution washing, and particle size classification; and / or post-processing the second calcined product to obtain a red fluorescent material.
[0013] According to another aspect of the present invention, a light-emitting device is provided, comprising the red fluorescent material of the present invention, or comprising the red fluorescent material obtained by the preparation method of the present invention.
[0014] Furthermore, the light-emitting device also includes a radiation source, which includes one or more of an ultraviolet emission source, a near-ultraviolet emission source and a blue light emission source; preferably, the light-emitting device also contains other phosphors, which include one or more of blue phosphors, cyan phosphors, yellow-green phosphors, red phosphors and infrared phosphors.
[0015] By applying the technical solution of the present invention, the two elements Sr and Ca are solid-dissolved in different proportions to form a series of red light-emitting materials with excellent photochromic properties, wherein the core adopts a silicon-aluminum-based nitride with a high Sr content, which can provide excellent luminous efficiency, and the shell adopts a silicon-aluminum-based nitride with a high Ca content, which can provide excellent resistance to water and oxygen erosion. The two work together to allow the red fluorescent material to take into account both high luminous efficiency and high reliability. Moreover, the core and shell of the red fluorescent material of the present invention are the same lattice structure, with low mismatch, stronger interface bonding force, and lower light efficiency loss. In summary, the red fluorescent material of the present invention has the comprehensive performance of excellent luminous efficiency, excellent encapsulation performance, and good reliability, and the light-emitting device prepared also has better reliability. Under high temperature and high humidity and long-term lighting, it can present higher light efficiency, better weather resistance, and more excellent light efficiency maintenance effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0017] Figure 1A schematic diagram of the particle structure of the red phosphor according to Example 1 of the present invention is shown, wherein D is the core diameter and d is the shell thickness;
[0018] Figure 2 A flow chart of a method for preparing a red phosphor according to Example 1 of the present invention is shown;
[0019] Figure 3 The morphology comparison photos of the red phosphor PCT before and after aging according to Comparative Example 1 are shown, wherein 3a is before aging and 3b is after aging;
[0020] Figure 4 The morphology comparison photos of the red phosphors according to Example 19 and Example 20 of the present invention are shown, wherein 4a is Example 19 and 4b is Example 20. DETAILED DESCRIPTION
[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0022] As described in the background of the present invention, the prior art has the problem that red fluorescent materials cannot achieve both high luminous efficiency and high reliability. In order to solve the above problem, in a typical embodiment of the present invention, a red fluorescent material is provided. The red fluorescent material is a core-shell structure, including a core and a shell coated on the surface of the core. The chemical composition of the core is represented by A1 m M1 a-m Al b Si c N d :xEu, the chemical composition of the shell is expressed as A2 n M2 a-n Al b Si c N d :yEu, wherein 0.92≤a≤1.2, 0.8≤b≤1.2, 0.8≤c≤1.2, 2.8≤d≤3.2; wherein A1 and A2 are independently selected from one or more of Ba, Mg, Li, Na and K, respectively, in the inner core, 0≤m≤0.02, 0.0001≤x≤0.08; M1 includes Sr and Ca, with the molar number of M1 being 1, the molar ratio of Sr to M1 is denoted as h, 0.6≤h<1; in the outer shell, 0≤n≤0.02, 0≤y≤0.03; M2 includes Sr and Ca, with the molar number of M2 being 1, the molar ratio of Ca to M2 is denoted as k, 0.6≤k≤1.
[0023] The red fluorescent material of the present invention is a CaAlSiN3 structure, which belongs to aluminum silicon-based nitride, which belongs to the cubic system, and the space group is Cmc21 (NO.36). Al atoms and Si atoms are randomly distributed in the same crystal lattice and produce covalent interactions with N atoms to form M6N 18 (M=Al,Si), its structure is composed of a three-dimensional network of interconnected (Si / Al)N4 tetrahedral structures, and has a very good rigid and stable structure.
[0024] The inventor unexpectedly found during the research that when Ca is the main element in the above structure, its energy is lower, the synthesis temperature is relatively low, the crystal structure is more stable, and it is not easy to be corroded by water and oxygen to cause structural collapse. 2+ The ionic radius is Left and right, Ca 2+ The ionic radius is Left and right, Sr. 2+ The larger the ion radius, the greater the volume expansion of the unit cell, and the gradually aggravated lattice distortion. Therefore, (Sr,Ca)AlSiN3 with a high Sr content has higher energy and is more susceptible to water and oxygen corrosion, causing structural collapse.
[0025] Based on this, in the red fluorescent material of the present invention, the chemical composition of the core is expressed as A1 m M1 a-m Al b Si c N d :xEu, M1 includes Sr and Ca, by limiting the molar ratio of Sr to M1 h to 0.6≤h<1, setting Sr as the main element of M1, its molar content accounts for ≥60% of M1, the position of Sr element substitution in M1 is more, the lattice structure undergoes microscopic changes, and Eu 2+ Being in a microscopic environment favorable for luminescence, the core can therefore provide higher luminescence efficiency.
[0026] The chemical composition of the shell is denoted as A2 n M2 a-n Al b Si c N d :yEu, M2 includes Sr and Ca. The molar ratio k of Ca in M2 is limited to 0.6≤k≤1, and Ca is set as the main element of M2, that is, its content is higher than that of Sr element, and the molar content accounts for ≥60% of M2. The outer shell is a solid solution of Ca mainly at the M2 position, and the lattice has relatively small expansion and lower energy. It can provide better resistance to water and oxygen erosion, act as a barrier to protect the inner core, block the erosion of water and oxygen to the inner core, and improve material reliability.
[0027] Moreover, in the red fluorescent material of the present invention, the core and the shell have the same lattice structure with a low mismatch, and it is easy to form the core structure first and then grow the shell. The interface bonding force is stronger. Compared with materials with inconsistent internal and external structures, it is easier to obtain a gradient of Ca component from low to high at the interface, thereby reducing the loss of light efficiency.
[0028] In the above silicon aluminum based nitride red fluorescent material, in addition to Sr, Ca, Al, Si, N, Eu elements, other chemical elements such as Ba, Mg, Li, Na, K and the like can be appropriately added as needed, as long as the original crystal structure is still maintained. The inventor unexpectedly found in the research process that adding a small amount of Ba, Mg, Li, Na, K elements to the core and shell of the fluorescent material of the present invention can ensure that the reliability is not affected while not affecting the main phase structure performance of (Sr, Ca) AlSiN3, and can also improve its luminous efficiency.
[0029] Moreover, for the constituent elements in the core and shell of the fluorescent material of the present invention, whether it is the core or the shell, when 0.92≤a≤1.2, 0.8≤b≤1.2, 0.8≤c≤1.2, 2.8≤d≤3.2 are satisfied, it is easy to obtain the required (Sr,Ca)AlSiN3 pure phase structure. In addition, Eu is used as an activator in the silicon-aluminum-based nitride red fluorescent material of the present invention. 2+ It exists, and its content in the core satisfies 0.0001≤x≤0.08. There may be no Eu activator or only a small amount of activator in the shell, that is, when 0≤y≤0.03 is satisfied, the luminescence concentration quenching can be well avoided, and better luminescence efficiency and reliability can be obtained. Due to the limitations of the preparation method in this field, the components of the shell and the core may inevitably contain a very small amount of oxygen element, but it does not affect the performance of the fluorescent material of the present invention. These are understandable to those skilled in the art and will not be repeated here.
[0030] In summary, the present invention comprehensively utilizes the advantages of high light efficiency and high reliability of the core and shell, which can not only greatly improve the overall reliability of the fluorescent material, but also further improve its luminous efficiency. The red fluorescent material of the present invention has the comprehensive performance of excellent luminous efficiency, excellent packaging performance, and good reliability. The light-emitting device made of it also has better reliability. Under high temperature and high humidity and long-term lighting, it can show higher light efficiency, better weather resistance and better light efficiency maintenance effect.
[0031] The red fluorescent material may be one or more of fluorescent powder, fluorescent film, fluorescent glass and fluorescent ceramic. The above types can better maintain the luminescent properties of the fluorescent material under high energy density, so the red fluorescent material of the present invention can also be applied to high-power devices.
[0032] In order to facilitate the phase formation of the material and further improve its luminescence performance and reliability, in a preferred embodiment, 0.003≤x≤0.08, 0.92≤a≤1.02, 0.8≤b≤1.01, and 0.98≤c≤1.01.
[0033] In a preferred embodiment, A1 and / or A2 is Na, that is, the core contains Na alone, the shell contains Na alone, or both the core and the shell contain Na, which has a more significant effect on improving the luminous efficiency. This is because Na is used as a doping ion in the aluminum silicon-based nitride of the present invention, and a small amount of Sr or Ca is substituted in the form of a monovalent unequal substitution, resulting in an unbalanced charge of the system. In this case, oxygen vacancies will be generated in the system to ensure the charge balance state of the system. The oxygen vacancies in the system can be used as a sensitizer to transfer energy to the activator Eu, which can enhance luminescence to a certain extent. On the other hand, the source of the Na element is usually sodium chloride, sodium carbonate, etc., which has a very low melting point, and can play a good fluxing effect on the aluminum silicon-based nitride, improve the grain morphology, and thus further improve the luminous efficiency.
[0034] To further improve the luminous efficiency of the fluorescent material, in a preferred embodiment, in the inner core, 0.8≤h≤0.99, the inner core is more easily phased within the above range, and a fluorescent material with a peak wavelength of 598-642nm and higher luminous efficiency can be obtained.
[0035] In a preferred embodiment, in the outer shell, 0.8≤k≤1, when the Ca element content is too low, it may lead to insufficient solid solution with CaAlSiN3 structure as the main structure, and slightly poor structural stability. When the molar ratio of the Ca element reaches 0.8 or above, its structure is less likely to collapse in a high temperature and high humidity environment, and the overall reliability of the fluorescent material is better improved.
[0036] For the purpose of obtaining better comprehensive performance of luminous efficiency and reliability, in a preferred embodiment, the diameter of the core is 4 to 32 μm, which has better luminous efficiency, is more suitable for white light LED packaging applications, and has better packaging light effect. Based on similar purposes, the thickness of the shell is further preferably 0.3 to 7 μm. If it is too thin, the isolation effect on water and oxygen is insufficient, and if it is too thick, the luminescence of the core is blocked, resulting in changes in the luminous coordinates or a decrease in the luminous efficiency.
[0037] In white light LED packaging, different fluorescent material grains are used. For different core grain sizes, the shell thickness needs to have a suitable ratio. In a preferred embodiment, the diameter of the core is 10-25 μm, and the ratio of the shell thickness to the core diameter is (0.03-0.2):1, thereby having better comprehensive performance of luminous efficiency and reliability.
[0038] In a preferred embodiment, in the shell, y is 0, and the ratio of the thickness of the shell to the diameter of the core is (0.01-0.1): 1. In the shell, y is 0, that is, the shell does not contain the activator Eu, and only has the matrix component of the CaAlSiN3 structure. The core provides a single luminescence, and the shell does not emit light. At this time, the shell only has the function of protecting and shielding the core. If the shell is too thick, the shielding effect is too serious, and the luminous efficiency and color coordinates are greatly affected. Therefore, the present invention limits the ratio of the thickness of the shell to the diameter of the core to (0.01-0.1): 1, so as to obtain better reliability while further maintaining a higher luminous efficiency.
[0039] On the basis of the above-mentioned silicon-aluminum-based nitride red fluorescent material of the present invention, a person skilled in the art can reasonably select a method well known to those skilled in the art to prepare the above-mentioned silicon-aluminum-based nitride red fluorescent material. In order to reduce the difficulty of the preparation operation, simplify the operation steps, and reduce the process cost, in another typical embodiment of the present invention, a method for preparing a red fluorescent material is also provided, comprising the following steps: Step S1, one or more nitrides, oxides and fluorides of Sr, one or more nitrides, oxides and fluorides of Ca, one or more nitrides, oxides and fluorides of Al, one or more nitrides, oxides and fluorides of Si, one or more nitrides, oxides and fluorides of Eu, and optional nitrides, oxides, fluorides and carbonates of alkali metals. One or more salts, optionally one or more nitrides, oxides, fluorides and carbonates of alkaline earth metals, are weighed and mixed according to the molar ratio of each element in the chemical composition of the inner core to obtain a first mixture; the molar ratio of each element in the chemical composition of the outer shell is weighed and mixed to obtain a second mixture; step S2, the first mixture is subjected to a first calcination to obtain a first calcination product; step S3, the first calcination product is mixed with the second mixture, and a second calcination is performed to obtain a red fluorescent material; wherein the alkali metal includes one or more of Li, Na and K, and the alkaline earth metal includes Ba and / or Mg.
[0040] The present invention first weighs and mixes the above raw materials according to the molar ratio of each element in the chemical composition of the inner core to obtain a first mixture with a high Sr content; and weighs and mixes the raw materials according to the molar ratio of each element in the chemical composition of the outer shell to obtain a second mixture with a high Ca content.
[0041] The first mixture is then subjected to a first calcination to synthesize a (Sr, Ca) AlSiN3 phase with a higher Sr content, providing excellent luminescence performance; based on this, it is mixed with the second mixture for a second calcination to synthesize a (Sr, Ca) AlSiN3 phase with a higher Ca content, providing excellent resistance to water and oxygen corrosion, thereby obtaining a core-shell structure red fluorescent material with good luminescence efficiency and high reliability, and the core and the shell have the same lattice structure with a low mismatch. The core structure is generated first and then the shell is grown, and the interface bonding force is stronger. Compared with the inconsistent growth method of the internal and external structures, it is easier to obtain a gradient of Ca content from low to high at the interface, which can greatly reduce the loss of light efficiency.
[0042] In the preparation process of the silicon-aluminum-based nitride red fluorescent material of the present invention, by synergistically regulating the components of the core and shell of the material, and further by synergistically regulating the core diameter and shell thickness of the material, the encapsulation performance and water-oxygen corrosion resistance of the luminescent material can be adjusted, thereby preparing a silicon-aluminum-based nitride red fluorescent material with high luminous efficiency and good reliability and excellent comprehensive performance. In addition, the preparation method of the present invention is simple and easy to implement, and the safety is significantly improved compared with existing surface modification methods such as inorganic coating and organic coating, and it is easy to promote to industrialization.
[0043] As mentioned above, the (Sr,Ca)AlSiN3 phase with a higher Sr content in the material core has higher energy and is therefore easier to synthesize at a higher temperature. In a preferred embodiment, in step S2, the first calcination temperature is 1500-2000°C, the time is 5-12 hours, and the atmosphere is nitrogen and / or hydrogen atmosphere, including three atmospheres, namely nitrogen atmosphere, hydrogen atmosphere, and nitrogen and hydrogen mixed atmosphere; preferably, the first calcination temperature is 1750-1930°C, and the above conditions are more conducive to the smooth phase formation of the core.
[0044] As described above, the (Sr,Ca)AlSiN3 phase with a higher Ca content in the material shell has lower energy, and a relatively low synthesis temperature can be used. In a preferred embodiment, in step S3, the second calcination temperature is 1300-1900°C, the time is 4-10 hours, and the atmosphere is nitrogen and / or hydrogen atmosphere; preferably, the second calcination temperature is 1500-1700°C, and the above conditions are more conducive to the smooth formation of the shell.
[0045] In the specific preparation process, in a preferred embodiment, the nitride of Al is AlN, the nitride of Si is Si3N4, and the nitride of Eu is EuN, and the phase effect is better. In order to further improve the quality of the silicon aluminum-based nitride red fluorescent material of the present invention, preferably, the preparation method also includes: post-processing the first calcined product, the post-processing includes one or more of ball milling, acid and / or alkaline solution washing, and particle size classification; and / or post-processing the second calcined product to obtain a red fluorescent material, preferably, the post-processing is acid and / or alkaline solution washing, the washing process can use weak acid and / or weak alkaline solution under different temperature environments, and the number of washing times can be 1, 2, 3, 4 or 5 times.
[0046] In another typical embodiment of the present invention, a light-emitting device is provided, comprising the red fluorescent material of the present invention, or the red fluorescent material obtained by the preparation method of the present invention. Since the red fluorescent material of the present invention has high thermal stability and easy control of the emission spectrum, it can take into account both high luminous efficiency and high reliability. Therefore, the light-emitting device or device using the red fluorescent material has high working stability, long service life, and is suitable for a variety of different needs.
[0047] Specifically, in a preferred embodiment, the light-emitting device further includes a radiation source, which includes one or more of an ultraviolet emission source, a near-ultraviolet emission source, and a blue light emission source; in order to further improve the light-emitting effect of the light-emitting device, preferably, the light-emitting device also contains other phosphors, which include one or more of blue phosphors, cyan phosphors, yellow-green phosphors, red phosphors, and infrared phosphors. The fluorescent material of the present invention is used in combination with the above-mentioned phosphors, so that the light-emitting device can emit white light with high light efficiency, high color rendering, and low color temperature, and these white light-emitting devices can be used in the field of lighting or display.
[0048] Among them, other phosphors can be (Y, Gd, Lu, Tb)3(Al, Ga)50 12 :Ce, (Mg,Ca,Sr,Ba)2Si04:Eu, (Ca,Sr)3Si05:Eu, (La,Ca)3Si6N 11 :Ce,a-SiA1ON:Eu, β-SiAlON:Eu, Ca3CaSc204:Eu, BaAl80 13:Eu, (Ca,Sr,Ba)Al204:Eu, (Sr,Ca,Ba)(Al,Ga,In)2S4:Eu, (Ca,Sr,Ba)3MgSi2O8:Eu / Mn, (Ca,Sr,Ba)2(Mg,Zn)Si2O7:Eu, Zn2SiO4:Mn, (Y,G d) BO3:Tb, ZnS:Cu,Cl / Al, ZnS:Ag,C1 / Al, (Sr,Ca)2Si5N8:Eu, (Li,Na,K)3ZrF7:Mn, (Li,Na,K)2(Ti,Zr)F6:Mn, (Ca,Sr,Ba)(Ti,Zr)F6:Mn,Ba 0.65 Zr 0.35 F 2.7 :Mn, (Sr,Ca)S:Eu, (Y,Gd)BO3:Eu, (Y,Gd)(V,P)O4:Eu, Y203:Eu, (Sr,Ca,Ba,Mg)5(PO4)3C1:Eu, (Ca,Sr,Ba)MgAl 10 O 17 :Eu, (Ca,Sr,Ba)Si202N2:Eu, 3.5Mg0·0.5MgF2·Ge02:Mn or one or more thereof.
[0049] Typically but not limiting, in the red fluorescent material, a is 0.92, 0.95, 0.98, 1.00, 1.02, 1.05, 1.08, 1.2 or a range consisting of any two of them, b is 0.8, 0.82, 0.85, 0.88, 0.90, 0.92, 0.95, 0.98, 1.00, 1.02, 1.05, 1.08, 1.2 or a range consisting of any two of them, c is 0.8, 0.82, 0.85, 0.88, 0.90, 0.92, 0.95, 0.98, 1.00, 1.02, 1.05, 1.08, 1.2 or a range consisting of any two of them, and d is 2.8, 2.9, 3.0, 3.1, 3.2 or a range consisting of any two of them.
[0050] Typically but not limiting, in red fluorescent materials, m is 0, 0.005, 0.01, 0.015, 0.02 or a range consisting of any two of them, x is 0.0001, 0.0005, 0.001, 0.005, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08 or a range consisting of any two of them, and h is 0.6, 0.7, 0.8, 0.9, 0.99 or a range consisting of any two of them.
[0051] Typically but not limiting, in red fluorescent materials, n is 0, 0.005, 0.01, 0.015, 0.02 or a range consisting of any two of them, y is 0, 0.005, 0.01, 0.015, 0.02, 0.025, 0.03 or a range consisting of any two of them, and k is 0.6, 0.7, 0.8, 0.9, 1 or a range consisting of any two of them.
[0052] Typically but not limiting, in the red fluorescent material, the diameter of the inner core is 4μm, 10μm, 15μm, 20μm, 25μm, 30μm, 32μm or a range consisting of any two of them, and the thickness of the outer shell is 0.3μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm or a range consisting of any two of them.
[0053] Typically but not limiting, in the red fluorescent material, when the diameter of the inner core is 10 μm, 15 μm, 20 μm, 25 μm or a range consisting of any two of them, the ratio of the thickness of the outer shell to the diameter of the inner core is 0.03:1, 0.05:1, 0.08:1, 0.1:1, 0.12:1, 0.15:1, 0.18:1, 0.2:1 or a range consisting of any two of them.
[0054] Typically but not limiting, in the red fluorescent material, when y is 0, the ratio of the thickness of the shell to the diameter of the core is 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1 or a range consisting of any two ratios thereof.
[0055] Typically but not limiting, in the preparation method of the red fluorescent material, in step S2, the temperature of the first calcination is 1500°C, 1550°C, 1600°C, 1650°C, 1700°C, 1750°C, 1800°C, 1850°C, 1900°C, 1930°C, 1950°C, 2000°C or a range consisting of any two of them, and the time is 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or a range consisting of any two of them.
[0056] Typically but not limiting, in the preparation method of the red fluorescent material, in step S3, the temperature of the second calcination is 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C, 1650°C, 1700°C, 1750°C, 1800°C, 1850°C, 1900°C or a range consisting of any two of them, and the time is 4h, 5h, 6h, 7h, 8h, 9h, 10h or a range consisting of any two of them.
[0057] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0058] Test method:
[0059] Element content: EDS (X-ray energy spectrometer) device, acceleration voltage 15kV, detection current 70μA.
[0060] Relative brightness, peak wavelength: spectrophotometer, excitation wavelength 460nm.
[0061] Packaging performance: The prepared red phosphor and yellow-green phosphor were evenly mixed into the packaging glue, and the solid-liquid mixture was coated on the blue LED chip, and then placed in a 100°C oven for drying. The packaging light efficiency, lumen, chromaticity coordinates and other performance tests were performed using the HAAS-2000 spectroradiometer of Hangzhou Yuanfang Company.
[0062] Powder reliability:
[0063] (1) Phosphor Accelerated Aging Test Method (PCT): Set the temperature, relative humidity, and pressure of the PCT accelerated aging test chamber to 121°C, 100%, and 2 atm, respectively. When the temperature, relative humidity, and pressure reach the above set values, place the phosphor sample in the chamber and store it for 1000 hours. Then take it out and cool it naturally to room temperature in a desiccator. Determine the relative brightness, chromaticity coordinates, or other related properties of the untreated sample and the PCT-treated sample, and use the absolute value of the difference between the two to represent the PCT aging performance of the tested phosphor. The color coordinate drift of the comparative example is used as a reference and is set to 100.
[0064] (2) Package into LED lamp beads for terminal testing: Place the components after the phosphor combination chip is packaged in a test box with 85% humidity and 85°C (double 85), pass 100mA current and 7V voltage, and perform long-term environmental degradation. Take them out after 1000h, and use the HAAS-2000 spectroradiometer of Hangzhou Yuanfang Company to perform performance tests such as packaged luminous efficiency, lumen, and chromaticity coordinates, and compare the parameter changes before and after degradation.
[0065] Comparative Example 1
[0066] According to the molecular formula Ca 0.11 Sr 0.84 Al 1.01 Si 0.99 N 3.1:0.05Eu Weigh the corresponding mass of Ca3N2, SrN2, AlN, Si3N4 and EuN, mix them evenly in a glove box isolated from water and oxygen, and bake them in a nitrogen atmosphere at 1900℃ for 10h to obtain an intermediate phosphor with a median particle size of about 29μm, and then perform post-dispersion treatment to obtain the final phosphor product. The photochromic properties are measured by a spectrophotometer under 460nm excitation, and the peak wavelength is about 642nm. The relative brightness is defined as 100%, and the color coordinate attenuation Δx after 1000h PCT accelerated aging is 100, see Table 1.
[0067] Comparative Examples 2 to 6
[0068] Referring to the preparation method of Comparative Example 1, according to the chemical formula composition of the target compound in each comparative example, the compound in appropriate amount is selected for mixing, grinding, and selecting appropriate roasting conditions to obtain the desired phosphor. The core size and light color data as well as the aging attenuation color drift data are shown in Table 1.
[0069] Example 1
[0070] According to the molecular formula Ca 0.13 Sr 0.85 Al 1.01 Si 0.99 N 3.1 :0.04Eu Weigh the corresponding mass of Ca3N2, SrN2, AlN, Si3N4 and EuN, mix them evenly in a glove box isolated from water and oxygen to obtain a first mixture, and perform a first calcination in a nitrogen atmosphere at 1910°C for 8h to obtain an intermediate phosphor with a median particle size of about 25μm as the first calcination product; according to the molecular formula Ca 1.02 AlSiN3:0.003EuAccurately weigh the corresponding mass of Ca3N2, AlN, Si3N4 and EuN, mix them to obtain a second mixture, mix the first calcined product with the second mixture in a mass ratio of 10:1, perform a second calcination at 1880°C in a nitrogen atmosphere for 10 hours, take out, crush, disperse, remove impurities, and dry to obtain a red phosphor. The shell thickness is about 2μm as determined by EDS spectrum analysis, and the peak wavelength is about 640nm and the relative brightness is 104% as measured by a spectrophotometer. The color coordinate attenuation Δx after 1000h of PCT accelerated aging is 15, see Table 1. The particle structure diagram of the red phosphor of Example 1 is shown in Figure 1 , where D is the core diameter and d is the shell thickness. The preparation method flow chart is shown in Figure 2 .
[0071] Examples 2 to 22
[0072] Referring to the preparation method of Example 1, according to the chemical formula composition of the core and shell target compounds in each example, appropriately measured compounds are selected for mixing, grinding, and appropriate roasting conditions are selected to obtain the corresponding red phosphor. The core size and shell thickness, light color data, and aging attenuation color drift data are shown in Table 1.
[0073] Embodiment 23
[0074] The difference from Example 1 is that the first mixture is subjected to a first calcination in a nitrogen atmosphere at 1500° C. for 12 hours to obtain an intermediate phosphor as a first calcination product; after being mixed with the second mixture, the mixture is subjected to a second calcination in a nitrogen atmosphere at 1300° C. for 10 hours to obtain a corresponding red phosphor. The core size and shell thickness, light color data, and aging attenuation color drift data are shown in Table 1.
[0075] Embodiment 24
[0076] The difference from Example 1 is that the first mixture is subjected to a first calcination at 1750°C in a nitrogen atmosphere for 8 hours to obtain an intermediate phosphor as a first calcination product; after being mixed with the second mixture, the mixture is subjected to a second calcination at 1500°C in a nitrogen atmosphere for 10 hours to obtain a corresponding red phosphor. The core size and shell thickness, light color data, and aging attenuation color drift data are shown in Table 1.
[0077] Embodiment 25
[0078] The difference from Example 1 is that the first mixture is subjected to a first calcination at 1930° C. in a nitrogen atmosphere for 8 h to obtain an intermediate phosphor as a first calcination product; after being mixed with the second mixture, the mixture is subjected to a second calcination at 1700° C. in a nitrogen atmosphere for 10 h to obtain a corresponding red phosphor. The core size and shell thickness, light color data, and aging attenuation color drift data are shown in Table 1.
[0079] Embodiment 26
[0080] The difference from Example 1 is that the first mixture is subjected to a first calcination in a nitrogen atmosphere at 2000°C for 5 hours to obtain an intermediate phosphor as a first calcination product; after being mixed with the second mixture, the mixture is subjected to a second calcination in a nitrogen atmosphere at 1900°C for 4 hours to obtain a corresponding red phosphor. The core size and shell thickness, light color data, and aging attenuation color drift data are shown in Table 1.
[0081] Comparative Example 1 PCT morphology comparison before and after aging photos see Figure 3 , where 3a is before aging and 3b is after aging. It can be seen that (Sr,Ca)AlSiN3 with high Sr content has higher energy and is more susceptible to water and oxygen corrosion, causing structural collapse.
[0082] The morphology comparison photos of the red phosphors of Example 19 and Example 20 are shown in Figure 4 , where 4a is Example 19 and 4b is Example 20. It can be seen that Na doping can improve the luminescence efficiency.
[0083] Table 1
[0084]
[0085]
[0086]
[0087] From the above, it can be seen that the embodiments of the present invention, by setting a silicon-aluminum-based nitride phosphor with a high Sr content in the core and a silicon-aluminum-based nitride phosphor with a high Ca content in the shell, simultaneously utilize the high luminous efficiency of high Sr nitride and the high reliability of high Ca nitride. The prepared phosphor has an improved or no reduction in relative luminous brightness when the peak wavelength is similar to that of the comparative example, and its anti-aging performance is greatly improved. After 1000h of PCT accelerated aging, the color coordinate drift is reduced by more than 60%, and the highest is close to 100%, achieving an effect of basically no attenuation.
[0088] Application Comparative Example 1
[0089] A 460nm blue LED chip was used as a radiation source, 0.068g of the phosphor of Comparative Example 1, 1.5g of aluminate yellow-green phosphor with a peak wavelength of about 531nm, 0.3g of encapsulation glue A, and 3g of encapsulation glue B were mixed evenly and coated on the 460nm LED chip, and a white light emitting device was obtained after curing, with a color coordinate x of 0.4400, y of 0.4040, Ra of 90.1, and a color temperature of 3002K. The LED lamp beads were connected to the lamp holder, placed in a test box with 85% humidity and 85℃ (double 85), and 100mA current and 7V voltage were passed through for a long time. After 1000 hours, the packaging light efficiency, chromaticity coordinates and other properties were tested using the HAAS-2000 spectroradiometer of Hangzhou Yuanfang Company. The luminous flux was defined as 100%, the light maintenance rate after 1000h was 91.6%, and the color drift Δu'v' was 88, see Table 2. The encapsulation glue A and the encapsulation glue B can be conventional types in the art.
[0090] Application Comparative Examples 2 to 4
[0091] Referring to the packaging method of comparative example 1, LED devices were packaged according to respective mass ratio schemes. The scheme, light color performance and light color data after aging are shown in Table 2.
[0092] Application Example 1
[0093] A 460nm blue LED chip was used as a radiation source, 0.068g of the phosphor of Example 2, 1.5g of aluminate yellow-green powder with a peak wavelength of about 531nm, 0.3g of encapsulation glue A, and 3g of encapsulation glue B were mixed evenly and coated on the 460nm LED chip, and a white light emitting device was obtained after curing, with a color coordinate x of 0.4401, y of 0.4039, Ra of 90, and a color temperature of 3000K. The LED lamp beads were connected to the lamp holder, placed in a test box with 85% humidity and 85℃ (double 85), and 100mA current and 7V voltage were passed through for a long time. After 1000 hours, the packaging light efficiency, chromaticity coordinates and other properties were tested using the HAAS-2000 spectroradiometer of Hangzhou Yuanfang Company. The luminous flux was defined as 100%, the light maintenance rate after 1000h was 98.8%, and the color drift Δu'v' was 9.
[0094] Application Examples 2 to 4
[0095] Referring to the packaging method of Application Example 1, LED devices were packaged according to respective mass ratio schemes. The scheme, light color performance and light color data after aging are shown in Table 2.
[0096] Table 2
[0097]
[0098]
[0099] From the above, it can be seen that after the LED lamp beads with similar coordinates are packaged with the comparison example with similar coordinates and the phosphor of the embodiment of the present invention and the blue light LED chip, and are subjected to lighting and aging for up to 1000 hours under the same conditions, compared with the application comparison example, the luminous efficacy of the lamp beads of each application embodiment of the present invention is slightly increased, the light maintenance rate is significantly increased, and the color drift is significantly reduced.
[0100] As can be seen from the above, compared with the comparative example, each embodiment of the present invention dissolves the two elements Sr and Ca in different proportions to form a series of red light-emitting materials with excellent photochromic properties, wherein the core adopts silicon-aluminum-based nitride with a high Sr content, which can provide excellent luminous efficiency, and the shell adopts silicon-aluminum-based nitride with a high Ca content, which can provide excellent resistance to water and oxygen erosion. The two work together to enable the red fluorescent material to take into account both high luminous efficiency and high reliability. Moreover, the core and shell of the red fluorescent material of the present invention have the same lattice structure, low mismatch, stronger interface bonding force, and lower light efficiency loss. In summary, the red fluorescent material of the present invention has the comprehensive properties of excellent luminous efficiency, excellent packaging performance, and good reliability, and the light-emitting device prepared also has better reliability. Under high temperature and high humidity and long-term lighting, it can present higher light efficiency, better weather resistance, and better light efficiency maintenance effect.
[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A red fluorescent material, characterized in that: The red fluorescent material is a core-shell structure, including a core and a shell coated on the surface of the core, and the chemical composition of the core is represented by A1 m M1 a-m Al b Si c N d :xEu, the chemical composition of the shell is expressed as A2 n M2 a-n Al b Si c N d :yEu, where 0.92≤a≤1.2, 0.8≤b≤1.2, 0.8≤c≤1.2, 2.8≤d≤3.2; wherein A1 and A2 are independently selected from one or more of Ba, Mg, Li, Na and K, In the core, 0≤m≤0.02, 0.0001≤x≤0.08; M1 is Sr and Ca, the molar number of M1 is 1, the molar ratio of Sr to M1 is recorded as h, 0.6≤h<1; In the shell, 0≤n≤0.02, 0≤y≤0.03; M2 is Sr and Ca, the molar number of M2 is 1, the molar ratio of Ca to M2 is recorded as k, and 0.6≤k≤1.
2. The red fluorescent material according to claim 1, characterized in that: A1 and / or A2 is Na; and / or In the kernel, 0.8≤h≤0.99; and / or In the shell, 0.8≤k≤1.
3. The red fluorescent material according to claim 1 or 2, characterized in that: The diameter of the inner core is 4-32 μm; and / or the thickness of the outer shell is 0.3-7 μm.
4. The red fluorescent material according to claim 3, characterized in that: The diameter of the inner core is 10-25 μm, and the ratio of the thickness of the outer shell to the diameter of the inner core is (0.03-0.2):
1.
5. The red fluorescent material according to claim 3, characterized in that: In the shell, y is 0, and the ratio of the thickness of the shell to the diameter of the core is (0.01-0.1):
1.
6. The method for preparing the red fluorescent material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1, weighing and mixing Sr nitride, Ca nitride, Al nitride, Si nitride, Eu nitride, and optional alkali metal nitride, and optional alkaline earth metal nitride according to the molar ratio of each element in the chemical composition of the inner core to obtain a first mixture; weighing and mixing according to the molar ratio of each element in the chemical composition of the outer shell to obtain a second mixture; Step S2, performing a first calcination on the first mixture to obtain a first calcination product; Step S3, mixing the first calcined product with the second mixture, and performing a second calcination to obtain the red fluorescent material; The alkali metal is selected from one or more of Li, Na and K, and the alkaline earth metal is selected from one or more of Ba and Mg.
7. The preparation method according to claim 6, characterized in that: In the step S2, the temperature of the first calcination is 1500-2000°C, the time is 5-12 hours, and the atmosphere is nitrogen and / or hydrogen atmosphere.
8. The preparation method according to claim 7, characterized in that: In the step S2, the temperature of the first calcination is 1750-1930°C.
9. The preparation method according to claim 6, characterized in that: In the step S3, the temperature of the second calcination is 1300-1900° C., the time is 4-10 hours, and the atmosphere is nitrogen and / or hydrogen atmosphere.
10. The preparation method according to claim 9, characterized in that: In the step S3, the temperature of the second calcination is 1500-1700°C.
11. The preparation method according to claim 6, characterized in that: The Al nitride is AlN, the Si nitride is Si3N4, and the Eu nitride is EuN.
12. The preparation method according to claim 11, characterized in that: The preparation method further includes: post-processing the first calcined product, wherein the post-processing includes one or more of ball milling, acid and / or alkaline solution washing, and particle size classification; and / or post-processing the second calcined product to obtain the red fluorescent material.
13. A light emitting device, characterized in that: The invention comprises the red fluorescent material according to any one of claims 1 to 5, or comprises the red fluorescent material obtained by the preparation method according to any one of claims 6 to 12.
14. The light emitting device according to claim 13, characterized in that: The light emitting device further comprises a radiation source, and the radiation source comprises one or more of an ultraviolet emission source, a near ultraviolet emission source and a blue light emission source.
15. The light emitting device according to claim 14, characterized in that: The light emitting device further contains other phosphors, which include one or more of blue phosphors, cyan phosphors, yellow-green phosphors, red phosphors and infrared phosphors.
Citation Information
Patent Citations
Nitric oxide luminous particle and preparation method thereof, nitric oxide luminous body and luminous device
CN105733571A
White light LED
CN110429169A